Perception and Experiences of Madrassah Education: An Anthropological study of Noorbakshi Madrassah - Arosa Hajira; Bibi Maryam; Bushra Zainab; Muhammad Asif; Noreen Fatima (Journal of Religion and Society, 2025)
This study explores the profound concepts of tazkiyah (self-purification) and personality development as illuminated through the life and teachings of the Prophet Muhammad ﷺ. Rooted in the Quranic principles and prophetic examples, the research highlights how the Seerah provides a comprehensive framework for the moral and spiritual refinement of individuals. Given the complex ethical, psychological, and social challenges of the modern era, this study investigates the relevance and application of these prophetic methods in addressing contemporary issues. Utilizing a qualitative, analytical approach, the research examines key incidents from the Seerah that exemplify the practical strategies of self-discipline, character formation, and ethical conduct. The findings emphasize the timeless importance of these teachings, demonstrating their potential to foster balanced and resilient personalities capable of navigating today’s societal complexities. This paper contributes to Islamic scholarship by bridging classical prophetic guidance with modern theoretical insights, offering practical implications for personal and community development in today’s world. Keywords: Seerah, Prophet Muhammad ﷺ, Tazkiyah, Personality Development